Sustainability or natural capital disinvestment? A retrospective on Brazilian economic growth, 1965-1993 - Torras, Mariano (Estudos Econômicos (São Paulo), 2000)
This paper evaluates the consequences of the Brazilian ‘economic miracle’ of the 1960s and 70s on the country’s natural environmental, with particular attention to two questions. First, to what extent did natural resource depletion - particularly Amazonian deforestation - after the economic miracle impact adversely on the opportunity for continued well-being improvements in Brazil? Second, was the government policy of targeting incentives toward investment in the Brazilian states in the North and Center-West economically sustainable in the long run? To address the first question, I use a ‘green accounting’ framework that corrects GDP growth for the value of depleted mineral, timber, and soil stocks, and apply it to Brazilian data from 1965 to 1993. For the second question, I base sustainability on whether gross capital formation exceeds the total value of resource depletion, and compare results under two alternative indicators for the same period. The results are generally inauspicious, especially in years subsequent to 1980, and cast considerable doubt on the efficacy of earlier government policies.